Hipotermia dan Waktu Pemulihannya dalam Anestesi Gas Isofluran dengan Induksi Ketamin-Xylazin pada Anjing (HYPOTHERMIA AND ITS RECOVERY IN GAS ISOFLURANE ANESTHESIA WITH KETAMINE-XYLAZINE INDUCTION ON DOGS) - Satria, Gagak Donny; Budhi, Setyo; Nurdyanti, Dinni (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
The most common effect occurred during anaesthesia is the decrease of body temperature. Technologicaldevelopment has enabled the used the latest innovations in order to to increase the efficacy and the safetyof anaesthesia. The purpose of this study was to determine the effect of ketamine-xylazine injection onhypothermia and its recovery at dog which anesthetized with isoflurane. Ten healthy dogs were dividedinto two groups with each group consisted offive dogs. In Group A, dogs were given premedication (atropinesulfate 0.04 mg/kg) and then anaesthetized with isoflurane gas (4% for induction dose and 1% for themaintenance dose). In Group B dogs were given premedication atropine sulfate (0.04 mg/kg) and ketamineHCl induction solution (10 mg/kg) mixed with xylazine HCl (2 mg/kg), and anaesthetized with isofluranegas (maintenance dose of 1%). Adaptation period was conducted in one week. Body temperature wasmeasured before, during, and after the duration of anaesthesia. The data was analyzed statistically by arepeated Anova test. This study found that the mean body temperature of dogs in Group A decreased from37,88±0,51 oC to 34,64±0,95 oC over a period of anaesthesia, and the recovery time was over 40 minutespost-anaesthesia. In Group B, body temperature decreased from 38.06±0.42 oC to 34.96±1.23 oC, and therecovery time was 90 minutes. In conclusion, the use of ketamine-xylazine in isoflurane anaesthesiaprocedures on dogs, would need post-anaesthesia preparation procedure regarding with hypothermia andits recovery.
Keywords: anaesthesia, isoflurane, ketamine, xylazine, temperature, recovery